Apakah Apakah pengeluaran pemerintah mempengaruhi Indeks Pembangunan Manusia di Provinsi Jawa Timur: Apakah pengeluaran pemerintah mempengaruhi Indeks Pembangunan Manusia di Provinsi Jawa Timur - Muslihatinningsih, Fivien; Alvidiar, Caren; Niken Wilantari, Regina (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2023)
This study aims to analyze the effect of government spending on the education, health and infrastructure sectors on the Human Development Index (IPM) in East Java. The variables used are HDI, government spending in the education, health and infrastructure sectors. This study uses secondary data in East Java in the form of quantitative data from 11 regencies in the Tapal Kuda Region and Madura Island in 2017-2021. The research data is sourced from the Central Bureau of Statistics and the Directorate General of Fiscal Balance. The data analysis method used is panel data analysis using the Fixed Effect Model (FEM) method. The results showed that government spending on the education and infrastructure sectors had a negative and significant effect on the HDI in East Java, while the health sector had a positive and significant effect on the HDI in East Java. Based on individual effect analysis, it shows that the effect of government spending on the education, health and infrastructure sectors is highest in Banyuwangi Regency. Meanwhile, the lowest influence was in Sampang Regency. Key Words: HDI, Govermen Spending, Education, Health, Infrastructure